Sorafenib-Loaded Nanoparticles Based on Biodegradable Dendritic Polymers for Enhanced Therapy of Hepatocellular Carcinoma - Li Z (Dove Medical Press, 2020)
Zihuang Li,1 Ling Ye,2 Jingwen Liu,1 Daizheng Lian,1 Xianming Li1 1Department of Radiation Oncology, The Second Clinical Medical College of Jinan University, Shenzhen Municipal People’s Hospital, Shenzhen 518020, People’s Republic of China; 2Department of Oncology, The First Affiliated Hospital of Jinan University, Guangzhou 510632, People’s Republic of ChinaCorrespondence: Zihuang Li; Xianming LiDepartment of Radiation Oncology, The Second Clinical Medical College of Jinan University, Shenzhen Municipal People’s Hospital, Shenzhen 518020, People’s Republic of ChinaTel +86 755 22942428Email li.zihuang@szhospital.com; li.xianming@szhospital.comPurpose: In spite of its enhanced efficacy and reduced side effects in clinical hepatocellular carcinoma (HCC) therapy, the therapeutic efficacy of antitumor angiogenesis inhibitor sorafenib (SFB) is still restricted due to short in vivo half-life and drug resistance. Here, a novel SFB-loaded dendritic polymeric nanoparticle (NP-TPGS-SFB) was developed for enhanced therapy of HCC.Methods: NP-TPGS-SFB was fabricated by encapsulating SFB with biodegradable dendritic polymers poly(amidoamine)-poly(γ-benzyl-L-Glutamate)-b-D-α-tocopheryl polyethylene glycol 1000 succinate (PAM-PBLG-b-TPGS).Results: NP-TPGS-SFB exhibited excellent stability and achieved acid-responsive release of SFB. It also exhibited much higher cellular uptake efficiency in HepG2 human liver cells than PEG-conjugated NP (NP-PEG-SFB). Furthermore, MTT assay confirmed that NP-TPGS-SFB induced higher cytotoxicity than NP-PEG-SFB and free SFB, respectively. Lastly, NP-TPGS-SFB significantly inhibited tumor growth in mice bearing HepG2 xenografts, with negligible side effects.Conclusion: Our result suggests that NP-TPGS-SFB may be a novel approach for enhanced therapy of HCC with promising potential.Keywords: dendritic block copolymer, sorafenib, enhanced therapy, TPGS, hepatocellular carcinoma